The Psychology of “Ultramodern” Art on the Essays by Gonzalo Rodríguez Lafora - Trujillo Arrogante, Pedro José (Eikón / Imago, 2019)
The aim of this paper is to approaches to the Gonzalo Rodríguez Lafora´s Psychology of Art on his context, which it was focused to research the sources and the effects of the artistic “Ultramoderm” inspiration and creation. Thus we will see factors have a bearing on the human purity, subjectivity, introspection or relation to the circumstances. We also are going to analyze the possible influences about how G. R. Lafora came to create his theory, focused to his stay in Germany where he met some of the most important figures inside of the psychiatry such Hans Prinzhorn and Emil Kraepelin. This work was published on five essays throughout the 10s and 20s of the last century.